GAMBARAN MODIFIABILITAS KOGNISI ANAK USIA DINI DI JAKARTA - Agustina Hendriati (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2015)
The study was conducted as a response to the lack of evidence-based practices of early childhood education and data on how-to-learn skills of children in Indonesia. The goal was to have a profile of cognitive modifiability of children in Jakarta. Forty-two upper level kindergarten children in five areas of Jakarta were selected representing variety of sex and social economic status. Subjects were assessed with the Application of Cognitive Function Scale using test-scripted mediation-retest. The result indicated that the children showing learning potential that is still under theoretical suggestion embedded in the scale. The discussions touched upon the property of the scale and the early childhood education practices in Jakarta.